Perception of the Varied Lecture Methods and Their Relationship to Tauhid Learning Outcomes of MDTA Class III Students - M Rizqy Al Fajri; Syuraini Syuraini (Universitas Negeri Padang, 2021)
This study aims to determine the students' perceptions of the varied lecture methods, to know the description of students' learning outcomes, and to find out the relationship between students' perceptions of the varied lecture methods and learning outcomes. This research is a correlational study with a quantitative approach. The subjects of this study were third grade students at MDTA Darul Hikmah. The population is 27 people and the sample is taken from the whole population using total sampling technique. The data collection tool in this study was a questionnaire. The data analysis techniques used in the study were percentage statistics and serial correlation. The results showed that the students' perceptions of the lecture learning method varied in the unfavorable category. The learning outcomes of students are also in the unfavorable category with an average score of 56.85 in the semester. The results of the price consultation r, it is concluded that r count is greater than r table, that is, there is a significant relationship between students' perceptions of the varied lecture learning method and learning outcomes.Keywords: Perception, Learning Methods, Learning Outcomes